Caecal schwannoma: a rare cause of per rectal bleeding in a 72-year-old man. (13th October 2014) - Dickson-Lowe, Richard A; James, Christopher L; Bailey, Charles MH; Abdulaal, Yasser
Abstract : The presence of per rectal (PR) bleeding in elderly people usually alerts us to the possibility of colonic malignancy, particularly if a concomitant altered bowel habit is present, without a history of the symptom. We present a case where the cause of PR bleeding turned out to be a caecal schwannoma. Caecal schwannoma is a rare tumour of the gastrointestinal tract of mesenchymal origin and diagnosis prior to radical surgical resection is difficult. Endoscopic biopsy often fails to provide an adequate specimen and immunohistochemistry is essential to the diagnosis.